Contribution of KH. MA. Sahal Mahfudh to Community Economic Empowerment - Prasetyoningrum, Ari Kristin; Darojat, Muhammad Irhas (Universitas Islam Indonesia, 2019)
This article aims to analyze the contribution of KH. MA. Sahal Mahfudh in empowering the economy of the community which is motivated by conditions of unresolved poverty. This article is a library research using a sociological-historical approach. Data collection methods in this study using documentation and interviews. The analysis of this research uses qualitative analysis. The results of this study indicate that the contribution of KH. MA. Sahal Mahfudh in community economic empowerment can be a solution to poverty problems. The Islamic boarding school led by Kiai Sahal has become the driving force for the economic empowerment program for the surrounding community by developing various business units. The business units established by Kiai Sahal include: BPR Artha Huda with conventional systems, BPR Artha Mas Abadi using the sharia system, printing businesses (Masda Grafika and Masda Digital Printing), Rambutan Gardens, and Walet Enterprises.